Suitability of microwave drying for mealworms (Tenebrio molitor) as alternative to freeze drying: Impact on nutritional quality and colour. (15th July 2018) - Lenaerts, S.; Van Der Borght, M.; Callens, A.; Van Campenhout, L.
Highlights: The impact of drying on the nutritional quality and colour of mealworms was studied. Microwave or freeze drying caused minor changes in the proximate composition. The fat quality of microwave dried larvae was better than that of freeze dried ones. Microwave drying is a good alternative to the current practice of freeze drying. The application of vacuum during microwave drying did not bring added value. Abstract: Freeze drying represents the current practice to stabilize mealworms, even though it is an energy demanding technique. Therefore, it was examined in the present study whether microwave drying could be a proper alternative. To this end, the impact of both drying techniques on the proximate composition, vitamin B12 content, fatty acid profile, oxidation status and colour parameters of mealworms was investigated. Furthermore, the influence of the application of vacuum during microwave drying was studied. The different drying technologies resulted in small differences in the proximate composition, while the vitamin B12 content was only reduced by microwave drying. The fat fraction of freeze dried mealworms showed a higher oxidation status than the fat of microwave dried mealworms. Application of a vacuum during the microwave drying process did not appear to offer advantages. This research shows that for mealworms microwave drying can be a proper alternative to freeze drying.